DESIGN INTERACTIVE ANIMATION RECOGNITION OF NUMBERS AND ALPHABETS FOR PLAYGROUP - DEVRI SUHERDI; Rita Hamdani (INFOKUM, 2022)
This study aims to make conventional learning more interesting for students in playing groups with the help of an educational game. Educational games made are interesting's animations. Animations should have bright colors and cute characters. The animations are about recognizing letters and numbers and training children's memory. This educational game is design interactively so that teachers can help children complete the game. The teacher gives directions so that the child can complete the game. This application is made using Adobe Flash CS3 and can be run with a flash player.